Therapeutic Sequencing in ALK+ NSCLC - Mei Elsayed; Petros Christopoulos (MDPI AG, 2021)
Anaplastic lymphoma kinase-rearranged non-small-cell lung cancer (ALK+ NSCLC) is a model disease for the use of targeted pharmaceuticals in thoracic oncology. Due to higher systemic and intracranial efficacy, the second-generation ALK tyrosine kinase inhibitors (TKI) alectinib and brigatinib have irrevocably displaced crizotinib as standard first-line treatment, based on the results of the ALEX and ALTA-1L trials. Besides, lorlatinib and brigatinib are the preferred second-line therapies for progression under second-generation TKI and crizotinib, respectively, based on the results of several phase II studies. Tissue or liquid rebiopsies at the time of disease progression, even though not mandated by the approval status of any ALK inhibitor, are gaining importance for individualization and optimization of patient management. Of particular interest are cases with off-target resistance, for example MET, HER2 or KRAS alterations, which require special therapeutic maneuvers, e.g., inclusion in early clinical trials or off-label administration of respectively targeted drugs. On the other hand, up to approximately half of the patients failing TKI, develop anatomically restricted progression, which can be initially tackled with local ablative measures without switch of systemic therapy. Among the overall biologically favorable ALK+ tumors, with a mean tumor mutational burden uniquely below 3 mutations per Mb and the longest survival among NSCLC currently, presence of the EML4-ALK fusion variant 3 and/or TP53 mutations identify high-risk cases with earlier treatment failure and a need for more aggressive surveillance and treatment strategies. The potential clinical utility of longitudinal ctDNA assays for earlier detection of disease progression and improved guidance of therapy in these patients is a currently a matter of intense investigation. Major pharmaceutical challenges for the field are the development of more potent, fourth-generation TKI and effective immuno-oncological interventions, especially ALK-directed cell therapies, which will be essential for further improving survival and achieving cure of ALK+ tumors.